Worlds of literacy (Multilingual Matters; Ontario Institute for Studies in Education, 1994)
This book is divided into five parts: Bringing together our worlds of literacy; Different voices: Handling multiplicities of literacy; Constituting identities; Choice and change; Collaboration and Resistance: Challenging words.